Topological control of extreme waves - Giulia Marcucci (Nature Portfolio, 2019)
Theories state that transitions between extreme waves are allowed but experimental confirmations are lacking because of lack of control strategies. Here, the authors propose and experimentally report, for the first time, the use of topological indices to control the generation of extreme waves.